Pengaruh Motivasi Kerja dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Global Internasional Industries Tangerang - Dudung Hadiwijaya; Ahmad Ahmad (JMB : Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of work motivation and work environment on employee performance at PT. Global International Industries Tangerang. This study uses a quantitative approach. The population in this study are employees at PT. Global International Industries Tangerang with a sample of 65 respondents. Sampling technique by method on probability sampling, with the determination of the sample purposive sampling. Data analysis techniques used are t test, f test and regression.The results of this study indicate that partially work motivation positive and significant effect on performance indicated by the value of tcount> ttable(8,879 > 1.674) and a significant of 0.000. For the work environment partially has a positive and significant effect on performance indicated by tcount> ttable (15,128 > 1.674) and a significant value of 0.000. Simultaneously work motivation and work environment have a positive and significant effect on performance indicated by the value of Fcount> Ftable(131,237 > 3.15) and a significant value of 0.000. The ability of the independent variables of work motivation and work environment to explain the contribution to performance is 80.9% as shown by the R square of 0.809 while the remaining 19.1% is influenced by other factors. With the value of the multiple linear regression equation Y = 2.255 + 0.231X1+0,729X2.